A Concurrent Mixed-Methods Study of Midwestern Latino Parents Participation and Preferences for Parenting Education Programs. - Ramos, Athena K.; Su, Dejun; Correa, Antonia; Trinidad, Natalia (Journal of Child & Family Studies, 2023)
Parenting programs are an important tool that can provide support for parents and families and improve family functioning. This concurrent nested QUANT + qual mixed methods study sought to better understand parenting education program participation and examine format, delivery, and content preferences for parenting programs among Latino parents in Nebraska. Results from a statewide survey (N = 173) indicated that 31.4% of parents in the sample had participated in a parenting program. Significant predictors of participation in parenting education programs included being unmarried, not working full-time, having a higher income, and having excellent or very good health. Major barriers to participation included lack of information about available programs and logistical concerns. Focus group participants discussed key program design concerns which included: (1) cultural clashes related to acculturation gaps between parents and children; (2) cultural relevance of programming; (3) logistical considerations; and (4) the inclusion of technology to enhance parenting. Overall, participants were particularly interested in group-based learning, flexible scheduling, and improving the cultural relevance of programs. Implications for program design and outreach to improve Latino parents' access and willingness to participate in parenting education programs are presented. Future research should explore the effectiveness of parenting program implementation and dissemination with Latino parents in rural communities, if there are differences in the benefits of parenting programs by Latino subgroup or level of acculturation, and assess the impact of near-peers in the delivery of parenting programs with Latinos. Highlights: Less than one third of Latino parents had participated in a parenting program. Parents' demographic characteristics like marital status, employment status, and income were associated with participation in parenting programs. Lack of information about available programs and logistical concerns were major barriers to participating in parenting programs. Programs should be culturally, linguistically, and contextually tailored to enhance the relevance for Latino communities. Dissemination and implementation science related to parenting program participation among diverse parents is needed.